Compressive Strength of Concrete Using Sorghum Husk Ash and Calcium Chloride (2020)
This paper investigated the effects of Sorghum Husk Ash (SHA) and Calcium Chloride (CaCl2) on the compressive strength of concrete. Concrete specimens were prepared by partial replacement of cement with SHA (5, 10, 15, 20 and 25% by weight) and addition of 1% CaCl2 by weight of binder; using a constant mix proportion (1:2:4) and water-to-binder ratio (0.6) for all mixtures. The properties evaluated were slump, density and compressive strength. The result indicated that addition of SHA reduced the slump (concrete turn out to be stiffer) and density of concrete. The 28 day compressive strengths result showed that 0%SHA/1%CaCl2 have the maximum strength of 28.11 N/mm2 followed by 5%SHA/1%CaCl2 (26.45 N/mm2), 10% (25.01 N/mm2), 0%SHA/0%CaCl2 (23.11 N/mm2), 15%SHA/1%CaCl2 (22.45 N/mm2), 20%SHA/1%CaCl2 (20.90 N/mm2) and 25%SHA/1%CaCl2 (18.13 N/mm2). This suggests that the best addition of SHA as fractional replacement for cement in CaCl2 concrete is in the range 0 - 20% since their compressive strength results were above 20 N/mm2 target strength. Incorporation of 1%CaCl2 together with 5 and 10%SHA would yield a concrete of greater compressive strength than standard concrete grade 20.